Oliver Tambo International Airport, South Africa: Land-Use Conflicts Between Airports and Wildlife Habitats - Robinson, Lance; Mearns, Kevin; McKay, Tracey (Frontiers in Ecology and Evolution, 2021)
Airports stimulate tourism and trade and are a vital link in any country’s tourism infrastructure and economy. Large airports such as South Africa’s busiest airport, the OR Tambo International Airport, in Ekurhuleni, Gauteng, are usually located on the periphery of cities, usually on land that forms part of the peri-urban economy, reserved perhaps for farming or left undeveloped. As a result, such land often becomes a wildlife haven within the more “urbanized” or developed areas. Unfortunately, this places wildlife, especially birds on a collision course with aircraft. So much so that bird and other animal strikes cost the aviation industry millions of US dollars annually. Therefore, it is essential to reduce the number of wildlife strikes, not only lower the risk of damage to aircraft, increase passenger safety and reduce operational delays, but also prevent a decline in local wildlife populations. Thus, this paper argues that South Africa must improve its management of land-use close to airports to minimize the potential for wildlife strikes. In that regard, this study catalogs the different habitats and land-use types surrounding OR Tambo International Airport, identifying potential bird hazard zones using kernel density analysis. This identifies which areas pose the highest risk of bird strikes. Although land-use and land zoning by the International Civil Aviation Organization (ICAO) recommends a 13 km buffer zone around airports, this study shows that land-use in the buffer zone must also take potential bird strikes into account. Thus, airport operators need to work with land-use planning authorities and neighboring stakeholders to do so.